Histórias de leitura : orientações e práticas de letramento literário - Sozza, Fatima Aparecida de Oliveira (2009)
This dissertation gives an account of the a research results of which corpora is constituted of personal reading accounts/histories of teachers, as reflection upon practices of literary literacy, experienced and recalled during significant activities at school, and out of it. The aims were the following: a) to investigate the way teachers of Portuguese language read literary texts, as well as to investigate the way such practice is influenced by orientations of literacy experienced by them concerning the readings they come across along their lives; b) to conduct a bibliographic study upon concepts of literacy and observe modulations applied to literary studies; c) to gather personal reading stories of the research participants, aiming at collecting practices of literary literacy; d) to verify if the literary reading of these participants are the results, or not, of various orientations of literacy along their lives: family, church, school, media, among others. This work analyzed the orientations of literary literacy present in the reading histories of language teachers of Portuguese as professionals directly involved with reader education, and gathered data of these same teachers' reading histories in order to comprehend the process of their education in reading. What have they read? What reading view they possess? How they deal with their practices of reading at the moment? The present research utilized a qualitative approach which may be comprehended as a specific activity of investigation aimed at reach certain interpretation of the reality. The research corpora is base on five texts produced by teachers of Assis Chateaubiand city, the western region of Paraná state. The data were collected by applying a written questionnaire, audio-recorded semi-structured interview, and the recall of reading histories of participants. Such data were analyzed based on a theoretical study upon literacy. From the 80's, to psychological and historical perspectives predominant on literacy studies and researches were added the social and ethnographic perspective. Besides the new principles and theoretical paradigms to the analyses of the phenomenon, two pairs of concepts are highlighted: on one side two models of literacy, that is, the autonomous and the ideological, and, on the other, the events and practices of literacy. The literary literacy is one part of the ideas of literacy which consist in the social uses of the literary text. We hope the results of this work to corroborate the criticisms and reflection and that the obtained data serve as a base for the discussions on literary literacy theme, and the readers education as well.